2019
DOI: 10.1080/09557571.2019.1596612
|View full text |Cite
|
Sign up to set email alerts
|

Ontological insecurities and the politics of contemporary populism

Abstract: The loss of faith in mainstream political parties and moderate electoral candidates seems characteristic of the zeitgeist in much of the Western world and beyond. Whether in the form of the United Kingdom's vote to exit the European Union (EU), the 2016 United States (US) presidential election of the Republican nominee Donald Trump, the prior strength of Senator Bernie Sandecrs within the Democratic party primaries, or the rise of the anti-neoliberal left alongside resurgent rightist anti-migration groups in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 14 publications
0
39
0
1
Order By: Relevance
“…However, several studies have identified a link between the increase in far-right populism and widespread perceptions of crises, insecurity, anxiety and alienation due to to a sense of loss of control -what Anthony Giddens 12 has termed a 'run-away world', defined by increased globalization and neoliberal reforms. 13 Here, the conceptual lens of ontological security 14 has opened for the scrutiny of not only the multitudes of fears and insecurities that lie at heart of populist politics and conflict, but also their gendered dimensions. 15 Ontological security refers to a 'security of being' and has to do with a person's elemental sense of safety in the world, where trust of others is like an emotional inocculation against existential anxieties, 16 whereas ontological insecurity refers to 'the consequent attempts to deal with … anxieties and dangers', where 'identity and autonomy are always in question'.…”
Section: Populism Ontological Insecurity and Gendered Narratives Of mentioning
confidence: 99%
“…However, several studies have identified a link between the increase in far-right populism and widespread perceptions of crises, insecurity, anxiety and alienation due to to a sense of loss of control -what Anthony Giddens 12 has termed a 'run-away world', defined by increased globalization and neoliberal reforms. 13 Here, the conceptual lens of ontological security 14 has opened for the scrutiny of not only the multitudes of fears and insecurities that lie at heart of populist politics and conflict, but also their gendered dimensions. 15 Ontological security refers to a 'security of being' and has to do with a person's elemental sense of safety in the world, where trust of others is like an emotional inocculation against existential anxieties, 16 whereas ontological insecurity refers to 'the consequent attempts to deal with … anxieties and dangers', where 'identity and autonomy are always in question'.…”
Section: Populism Ontological Insecurity and Gendered Narratives Of mentioning
confidence: 99%
“…This common starting point notwithstanding, IR research on ontological security is characterized by increasing diversity with constructivist (Berenskoetter, 2014; Berenskoetter and Giegerich, 2010; Flockhart, 2016), post-structuralist (Browning, 2019; Eberle, 2019; Kinnvall, 2004, 2018), and post-colonial (Agius, 2017; Shani, 2017; Untalan, 2020; Vieira, 2018) approaches being developed. Recently, this internal heterogeneity seems to have prompted a terminological shift away from Ontological Security Theory (OST), a label that might be taken to imply a single standardized theory, toward OSS (Donnelly and Steele, 2019; Steele, 2019; Steele and Homolar, 2019) as a way to better capture the plurality of approaches. Irrespective of the precise denomination, however, ontological security has proved fruitful for addressing a wide variety of theoretical and empirical concerns.…”
Section: Ontological Security In International Relationsmentioning
confidence: 99%
“…Irrespective of the precise denomination, however, ontological security has proved fruitful for addressing a wide variety of theoretical and empirical concerns. It has allowed scholars interested in status (Pacher, 2019; Zarakol, 2010, 2011), revisionism (Behravesh, 2018), ideology (Marlow, 2002), and nationalism (Kinnvall, 2004; Skey, 2010) to enter into a conversation with scholars working on identity practices (DeRaismes Combes, 2017), material environments (Ejdus, 2017, 2020), collective memory (Gustafsson, 2014; Mälksoo, 2015; Subotić, 2019), transitional justice and reconciliation (Gustafsson, 2020; Mälksoo, 2019; Rumelili, 2018), diasporas (Abramson, 2019; Kinnvall and Nesbit-Larkin, 2009), regionalism (Russo and Stoddard, 2018), foreign policy (Darwich, 2016; Lupovici, 2012; Mitzen and Larson, 2017; Oppermann and Hansel, 2019), power transitions (Chacko, 2014; Young, 2017), popular protests (Solomon, 2018), populism (Browning, 2019; Kinnvall, 2018; Steele and Homolar, 2019), or security communities (Berenskoetter and Giegerich, 2010; Greve, 2018). Thus, ontological security scholarship has certainly succeeded in inaugurating a new research agenda and in generating new interpretations of a great variety of issues in international politics.…”
Section: Ontological Security In International Relationsmentioning
confidence: 99%
“…Fifth, and finally, our argument can help us understand the politics of populism and foreign policy, currently an area of growing interest (Destradi and Plagemann, 2019;Steel and Homolar, 2019; REFERENCE ANONYMISED). The insider-outsiders we describe are not substantively dissimilar from many populist leaders today, who have similar trajectories to power and who equally view strategic change as a means of promoting a new identity between state and society.…”
Section: Discussionmentioning
confidence: 91%